VCP/p97 Is a Proviral Host Factor for Replication of Chikungunya Virus and Other Alphaviruses - Carissimo, Guillaume; Chan, Yi-Hao; Utt, Age; Chua, Tze-Kwang; Bakar, Farhana Abu; Merits, Andres; Ng, Lisa F. P. (Frontiers in Microbiology, 2019)
The evolutionarily conserved AAA+ ATPase valosin-containing protein (VCP) was previously shown to be a proviral host factor for several viruses from different viral families such as Flaviviridae, Picornaviridae, and Herpesviridae. VCP was shown to affect trafficking of Sindbis virus receptor and functions as a component of Semliki Forest virus (SFV) replicase compartment. However, the role of this cellular protein was not evaluated during replication of alphaviruses including chikungunya virus (CHIKV). Using siRNA, chemical inhibitors, and trans-replication assays, we show here that VCP is a proviral factor involved in the replication of CHIKV. Immunofluorescence assays confirmed that VCP co-localized with non-structural replicase proteins but not with dsRNA foci possibly due to VCP epitope unavailability. VCP pro-viral role is also observed with other alphaviruses such as o’nyong’nyong virus (ONNV) and SFV in different human cell lines. VCP proviral roles on several viral families now extend to replication of alphaviruses CHIKV and ONNV, emphasizing the pivotal role of VCP in virus–host interaction biology.